2012
DOI: 10.5267/j.msl.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study to measure the relative efficiency and strategic planning using BSC-DEA and DEMATEL

Abstract: Performance evaluation is one of manager's main concerns in today competitive world, which covers all aspects and dimensions of organization and it is adequately flexible and measurable. So, the necessity of performance evaluation application for organizations where their intangible assets are higher than tangible ones, such as educational institutions, is more obviously observed. Balanced scorecard (BSC) is discussed by the aim of promoting manager's decision making and directing their attention toward extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…DEMATEL is used because it helps to clearly describe complex systems, to analyse cause-effect influences that may exist between two variables, to identify strengths and weaknesses of strategic objectives; it can design strategic maps to improve strategic mapping processes; it can choose and rank criteria to accomplish at a more efficient and effective management in an organization; for example, it can be applied to innovate in ICTs and control systems (Chiu et al, 2006;Falatoonitoosi et al, 2013;Hemati et al, 2012;Moghaddam et al, 2011;Sumrit & Anuntavoranich, 2013). The model is a strong decision method that permits the integration of expert opinion to evaluate management by grouping cause and effect indicators in the context of Balanced Scoredcard (Malina et al, 2007;Wu, 2012;Wu & Lee, 2007).…”
Section: Brief Bibliographic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…DEMATEL is used because it helps to clearly describe complex systems, to analyse cause-effect influences that may exist between two variables, to identify strengths and weaknesses of strategic objectives; it can design strategic maps to improve strategic mapping processes; it can choose and rank criteria to accomplish at a more efficient and effective management in an organization; for example, it can be applied to innovate in ICTs and control systems (Chiu et al, 2006;Falatoonitoosi et al, 2013;Hemati et al, 2012;Moghaddam et al, 2011;Sumrit & Anuntavoranich, 2013). The model is a strong decision method that permits the integration of expert opinion to evaluate management by grouping cause and effect indicators in the context of Balanced Scoredcard (Malina et al, 2007;Wu, 2012;Wu & Lee, 2007).…”
Section: Brief Bibliographic Analysismentioning
confidence: 99%
“…DEMATEL concept has been used since 1972 for quantitative processing of people's perceptions, to help represent and analyze mental maps of information according to the requirements and objectives defined by the organization being a priority the effective use of information where knowledge and reasoning have a very important role. It has been associated with a problem-solving method for evaluating qualitative-quantitative information (Chiu et al, 2006;Hemati et al, 2012;Moghaddam et al, 2011). In this article model will be the main theme.…”
Section: Introductionmentioning
confidence: 99%
“…In the following related literatures, Hemati, Danaei, and Shahhosseini () used DEMATEL and BSC‐DEA to measure the relative efficiency of DMUs; Alinezhad and Simiari () considered the problem of project selection via DEMATEL and DEA; Chen, Wu, and Kuang () evaluated the enterprises' green growth efficiency based on DEMATEL–DEA; Khalili‐Damghani and Molayee () combined DEMATEL and DEA to measure the performance of detection and governmental punitive agency. These researches are similar to the proposed concept of the links for DEMATEL–DEA, but we consider the links through DEMATEL‐based network DEA to represent the realistic evaluating performance situations of the financial holding companies in Taiwan; that is, DEMATEL is to identify the input, intermediator, and output variables that are used in network DEA for efficiency measurement.…”
Section: Introductionmentioning
confidence: 99%
“…In the following related literatures, Hemati, Danaei, and Shahhosseini (2012) used DEMATEL and BSC-DEA to measure the relative efficiency of DMUs; Alinezhad and Simiari (2013) considered the problem of project selection via DEMATEL and DEA; Chen, Wu, and Kuang (2015) evaluated the enterprises' green growth efficiency based on DEMATEL-DEA;…”
mentioning
confidence: 99%
“…Khaki, Najafi, and Rashidi (2012) explored financial and non-financial performance in the banking industry using a DEA-BSC approach and found that both efficient and inefficient units could be determined. Hemati, Danaei, and Shahhosseini (2012) used this model in higher education by measuring the relative importance of various university units and concluded that different units were efficient in different areas.…”
Section: Dea-bscmentioning
confidence: 99%